PENGARUH PENGGUNAAN LKS BERORIENTASI STRATEGI LEARNING STARTS WITH A QUESTION DENGAN MENGINTEGRASIKAN NILAI KARAKTER TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI SMAN 6 PADANG - Ridha Arahmi Oktavia (PILLAR OF PHYSICS EDUCATION, 2014)
Objective of this research is to determine the effect of using worksheet based Learning Starts With A Question by integrating the character value to physics learning outcomes of 11th grade students in SMAN 6 Padang. Type of research is quasi-experiment with Randomized Control Grup Only Design. A superior class as population of this research is All of 11th grade students in SMAN 6 Padang in academic 2013/2014 except IPA 1. Data of learning outcomes was data of this research. The mean equality test is a way to analyze the data. From of analyzis of data, we can conclude that there was a significance effect of using the worksheet based Learning Starts With A Question to learning outcome of 11th grade students in SMAN 6 Padang for domain cognitive, domain affective, and character values at significance level 5%